Anatomy of the Rally Round the Flag Effect - Georgarakis, George (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2021)
When national security is breached, citizens systematically increase their trust in the political system and the head of state, in particular. This effect is dubbed “rally ‘round the flag.” For almost 50 years, research has been investigating the paradox of why public opinion rewards its leadership, despite the failure of the latter to protect the citizens. This review aggregates and critically revisits recent literature on the rally ‘round the flag effect. To provide a systematic account of the literature, a classification is proposed, which accounts for the top-down and bottom-up interpretations that are offered from a rational choice perspective, and political psychology. This study highlights the significance of applying an integrative approach to advance a comprehensive understanding of the rally ‘round the flag effect.